Comparative Study between Jigsaw 1 Model and Picture Composition to Enhance Students’ Ability in Writing Descriptive Text - Nining Safitri, Debora Chaterine Simanjuntak, (LPPM Universitas Advent Indonesia, 2018)
This study addresses to see the significant difference between those who were taught using Jigsaw 1 model and those who were taught using picture composition to enhance the students’ ability in writing descriptive writing. This cooperative study involved two groups. Sample of this research were the students of X-A using Jigsaw 1 Model and X-B using Picture Composition at SMA Negeri 1 Parongpong. This study utilized essay Anatest, Microsoft Excel and 23rd SPSS to calculate the data. From the data analysis for Jigsaw 1 Model group, the mean score of gain in pre-test and post-test is 0.4680 and for Picture Composition group, the mean score of gain in pre-test and post-test is .5381. Based on the analysis, it is concluded that there is significant difference between those who were taught using Jigsaw 1 Model and Picture Composition in enhancing High School students’ ability in descriptive writing. Keywords: Jigsaw 1 Model, Picture Composition, Descriptive Writing